Enhancing Students' Critical Thinking Skills through Generative Model Learning Materials Assisted by PhET - Abdul Quddus; Gunawan Gunawan; Sutrio Sutrio (Indonesian Journal of STEM Education, 2024)
This research and development study aimed to produce learning materials based on a generative model assisted by PhET simulations to enhance students' critical thinking skills. The 4D development model (Define, Design, Develop, Disseminate) was employed. The developed products included a syllabus, lesson plans (RPP), teaching materials, student worksheets (LKPD), and a critical thinking skills assessment instrument. The validity of the products was evaluated by six validators using a Likert scale, practicality was assessed through student response sheets, and effectiveness was measured by the improvement in pretest-posttest scores using the N-Gain test. The results showed that the developed learning materials were highly valid (89.14%) and reliable (94.00%) based on validator assessments, and practical (72%) based on student responses. However, the improvement in students' critical thinking skills was moderate (N-Gain 0.43), indicating less than optimal effectiveness of the materials.